OPTIMIZATION OF A LASER TELEMETRIC SYSTEM PHOTORECEIVING MODULE - K. V. Melnikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Different types of schematic solution to design optical-to-electronic signal transforming stages are considered. Possible alternatives for laser telemetric system photoreceiver module building are analyzed. Designed device based on presented algorithm nanosecond pulses photoreceiving is presented. Parameters of the photoreceiver module are given.